1974
DOI: 10.1016/0042-6989(74)90209-0
|View full text |Cite
|
Sign up to set email alerts
|

Opponent-process additivity-I: Red/green equilibria

Abstract: Abstract-A red/green equilibrium light is one which appears neither reddish nor greenish (i.e. either uniquely yellow, uniquely blue, or achromatic). A subset of spectral and nonspectral red/green equilibria was determined for several luminance levels, in order to test whether the set of all such equilibria is closed under linear color-mixture operations.The spectral loci ofequilibrium yellow and blue showedeither no variation or visually insignificant variation over a range of l-2 log,, unit. There were no tr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

9
47
1

Year Published

1975
1975
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 152 publications
(57 citation statements)
references
References 12 publications
9
47
1
Order By: Relevance
“…Stimuli were delivered for 1 set with an intertrial interval of 20 set of darkness. Wavelengths required for equilibrium were determined by staircase procedures (Larimer et al, 1974 with luminance approximately constant. Staircases for three or more conditions were irregularly infersper&, thereby avoiding anticipatory responses.…”
Section: Methodsmentioning
confidence: 99%
“…Stimuli were delivered for 1 set with an intertrial interval of 20 set of darkness. Wavelengths required for equilibrium were determined by staircase procedures (Larimer et al, 1974 with luminance approximately constant. Staircases for three or more conditions were irregularly infersper&, thereby avoiding anticipatory responses.…”
Section: Methodsmentioning
confidence: 99%
“…Linear expressions provide acceptable fits to the experimentally determined hue cancellation functions upon which the quantitative model was originally based; hence, they are used in this presentation. Outcomes of experimental tests by a number of investigators are consistent with linearity for the red/green chromatic channel, although for the yellow/blue channel departures from linearity have been found that seem to vary in degree from one observer to the next (16)(17)(18)(19)(20). Because the test measures used as the index of adaptation and recovery in the experiments reported here involve only the red/green system, we can accept the linear relation as an adequate.…”
Section: Discussionmentioning
confidence: 69%
“…30 However, not all the evidence is consistent with a close linkage between retinal performance and color experience. Color-naming, at least, seems to be decoupled or insulated from other stages in visual processing.…”
Section: Discussionmentioning
confidence: 90%